Chloroplast DNA variation and genetic structure of Miscanthus sinensis in southwest China. (February 2015) - Yan, Haidong; Zhang, Xinquan; Fu, Chen; Huang, Linkai; Yin, Guohua; Nie, Gang; Xu, Wenzhi; Liu, Xinchun; Chen, Tao; Lee, Samantha; Ma, Xiao; Peng, Yan; et al.
Abstract: Miscanthus sinensis is a dominant perennial C4 grass with the potential to being a feedstock crop in North America, Europe, and China. Variation in chloroplast DNA sequence was used to obtain information regarding the genetic diversity and structure of populations of M. sinensis in southwest China. Chloroplast DNA, trnL-F and rpl20-rps12 sequences from seventy-five individuals representing 14 populations of M. sinensis were used to study the sequence variation. Seven haplotypes and 16 polymorphic sites (2.7%) were identified. Five substitutions, 6 indels, and 5 existing substitutions and indels sites, were detected through splicing these two gene segments. The genetic diversity within the studied populations (diversity of haploids, h = 0.561, nucleotide diversity, π = 0.00504) was low, this may be affected by the relatively larger effect of genetic drift on the chloroplast DNA, reflecting smaller effective populations than nuclear DNA. Genetic variance within the populations was higher than that between the populations, suggesting that higher gene flow may exist within these populations. The results of parsimony network in seven haplotypes indicated that H1 and H2 may be ancient haplotypes, which may help guide future research on the origin of M. sinensis . Our results provide information on the genetic diversity and structure of M. sinensis and may assist future studies on the phylogeography of M. sinensis . Highlights: Chloroplast DNA was used for exploring genetic diversity in Miscanthus sinensis . Fourteen populations expressed low genetic diversity and high rate of gene flow. AMOVA showed that most of genetic variance occurred within populations.